Pengaruh Kualitas Produk Terhadap Kepuasan dan Loyalitas Pelanggan pada Pelanggan Batik Batam di Dekranasda Kota Batam - Salma Putri Effendi; Emron Edison (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2022)
The purpose of this study was to determine the effect of product quality on customer satisfaction and customer loyality in batik Batam customers of Dekranasda Batam City. This research conducted at building of Dekranasda Batam city, this building also Galery of Dekranasda Batam City and Office of Dekranasda secretariat. This type of research is explanatory research with a quantitative method approach. This research was conducted by distributing quetionnaires to 336 respondents. Data analysis using descriptive and verification analysis, the analysis model used is a simple linear regression test. Data management using the windows version of SPSS software. Based on the result of the descriptive analysis test, it was found that the value of the product quality variabel with an average 4,52 was in the “Very good” category. obtained the value of customer satisfaction variable with an average 4,53 was in the “Very good” category. obtained the value of customer loyality variable with an average 4,46 was in the “Very good” category. While the result of the verification analysis of product quality variables on customer satisfaction obtained a t-count of 22,770, greater the t-table, namely 1,967 with a significance value of 0,00<0,05, wich mean that the product quality partially (t-test) has a positive and significant effect on customer satisfaction. The result of the verification analysis of product quality variables on customer loyality obtained a t-count 17,560, greater the t-table, namely 1,967 with a significance value of 0,00<0,05, wich mean that the product quality partially (t-test) has a positive and significant effect on customer loyality. The results of the calculation show that the coefficient of determination product quality variables on customer satisfaction is 0,608 or 60,8%, meaning that customer satisfaction is influenced by product quality of 0,608 or 60,8%, while the results of the calculation show that the coefficient of determination is 0,480 or 48%, meaning that customer loyality is influenced by product quality of 0,48 or 48%.